Cerebral insufficiency and mechanisms of decline of efficiency of integrative ability of cerebrum - G. A. Shifrin; K. V. Serikov (Zaporozhye State Medical University, 2013)
Integrative ability of cerebrum of patients with an ischemic stroke and small ischemic stroke is characterized stress stability. Hyperosmolarity is the predictor of head cerebral edema, which shows up the increase of intracranial pressure and proof violation of consciousness.